SYNTHESIS OF SULPHONATED MESOPOROUS SILICA FROM RICE HUSK ASH (Oryza sativa L.) - Maylina, Ajeng Chandra; Subagyono, R.R. Dirgarini Julia Nurlianti; Daniel, Daniel (Jurusan Kimia FMIPA UNMUL, 2018)
A study on the synthesis of sulphonated mesoporous silica from rice husk ash (Oryza sativa L.) been conducted. The preparation of sulphonated MSU-H was conducted by several steps namely, extraction of silica from rice husk ash, synthesis of mesoporous silica, synthesis of sulphonated mesoporous silica with post-grafting method. The N2 adsorption-desorption characterization results show the surface area of mesoporous silica 134 m2/g, pore volume 0.81 cm3/g and pore size 24.13 nm. The FT-IR characterization results of sulphonated mesoporous silica indicate the presence of Si-O-Si, Si-O, O-H and C-H alkane clusters.